Effects of Separated Fractions of FBC Bottom Ash on Selected Properties of Cement Mortars - Kledyński, Zbigniew; Krysiak, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper discusses the effects of partial replacement of cement with fluidized bed bottom ash on the properties of mortars. The analyzed ash samples originating from four Polish power plants were separated by grain size selection into fine and coarse-grained fractions. This process leads to a creation of derivative samples of differing physical properties and, partially, phase compositions, as tested in XRD and TG analyses.
Keywords: bottom ash; grain size; cement mortar; physical properties; fluidized bed; popiół denny; wielkość ziarna; zaprawa cementowa; właściwości fizyczne; środowisko wodne